If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -1(2c + -3) = 2(c + 3) + c Reorder the terms: 24 + -1(-3 + 2c) = 2(c + 3) + c 24 + (-3 * -1 + 2c * -1) = 2(c + 3) + c 24 + (3 + -2c) = 2(c + 3) + c Combine like terms: 24 + 3 = 27 27 + -2c = 2(c + 3) + c Reorder the terms: 27 + -2c = 2(3 + c) + c 27 + -2c = (3 * 2 + c * 2) + c 27 + -2c = (6 + 2c) + c Combine like terms: 2c + c = 3c 27 + -2c = 6 + 3c Solving 27 + -2c = 6 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 27 + -2c + -3c = 6 + 3c + -3c Combine like terms: -2c + -3c = -5c 27 + -5c = 6 + 3c + -3c Combine like terms: 3c + -3c = 0 27 + -5c = 6 + 0 27 + -5c = 6 Add '-27' to each side of the equation. 27 + -27 + -5c = 6 + -27 Combine like terms: 27 + -27 = 0 0 + -5c = 6 + -27 -5c = 6 + -27 Combine like terms: 6 + -27 = -21 -5c = -21 Divide each side by '-5'. c = 4.2 Simplifying c = 4.2
| y+15.2=-4.5 | | 10x-4+6x=18 | | 7a+6a+7b-6b-10a= | | 3x-4.2=9.4 | | 8s-240=72 | | (6x)(3x+2)=y | | B+23m=342 | | -2p+4(1-p)=8p-2(1-p) | | 4+3a=22+a | | 4(5x+2)-8(x-6)=62 | | 2Q+D=48 | | B+10m=147 | | 7g-2h=-9 | | -2-16=3(h-2) | | 90+(5x-6)+3x=180 | | 2x+10-4x=-3 | | 4x+5=(-11) | | Y=5(3x-3)+2 | | 3/4(2x-4) | | B+10m=342 | | lnx^5=1 | | 21x/7-5x=24 | | 5/6(-2)p | | 2y/3-14/15=y/5 | | 27m^3+9m^2-12m-4=0 | | x^(11/19)=3 | | 5/6-2p | | GraphX-8y=9 | | 2x(2x-3)=6+x | | 5(4x-9)-7=5(x-3)+38 | | y^2+12y=-x^2-4x+16 | | 2p+-14p+16p=-4 |